A rare case of intra-renal paraganglioma in a child masquerading as renal cell carcinoma - Aditya Arvind Manekar; Subrat Kumar Sahoo; Bikasha Bihary Tripathy; Prasant Nayak; Mukund Namdev Sable; Manoj Kumar Mohanty (Wolters Kluwer Medknow Publications, 2023)
Background: Renal cell carcinomas (RCCs) are rare in children, accounting for around 2% of all pediatric renal tumors. Paragangliomas are extra-adrenal locations of phaeochromocytomas. They originate from chromaffin cells arising along the sympathetic paraganglia and are secretory in most cases. Sequential imaging is often required to ascertain the etiology of a renal mass; ultrasound (USG), contrast-enhanced computerized tomography scan (CECT), and magnetic resonance imaging (MRI). Tissue diagnosis is confirmatory. Clinical Description: An 11-year-old girl presented with a right-sided abdominal and flank pain that was dull aching and nonradiating. She had no history of jaundice, hematuria, dysuria, bowel symptoms, sweating, palpitations, or syncope. The vitals were stable, without tachycardia or hypertension. No abnormal findings were found on clinical examination. Initially, the possibility of a renal stone was considered. Management and Outcome: Baseline blood tests were normal. Abdominal USG detected a heterogeneous mass in the right kidney. CECT ascertained that it was very vascular and exhibited contrast enhancement, suggesting a renal tumor. MRI showed that the right renal artery was acting as the feeding vessel to the tumor. RCC was suspected based on imaging. The vascular nature prevented us from performing a Tru-cut biopsy. A right-sided nephrectomy was planned, preceded by angiography and embolization of the right renal artery to reduce vascularity. Intraoperative episodes of hypertension were noted. Gross appearance suggested RCC; however, histopathology revealed evidence of an intrarenal PGL. Conclusions: Diagnosing a nonfunctional PGL in an asymptomatic patient is challenging and may only be possible by intraoperative histopathology.